ROLE OF LEADERSHIP AND CLAN CULTURE DURING PANDEMIC COVID-19: CAN IT CREATE LOYALTY? - Mahendra Fakhri (Jurnal Sosioteknologi, 2022)
The research empirically tests how organizational culture and democratic leadership style affect Small Music Studio Business employee loyalty. The method used in this research is a quantitative method with descriptive and causal research objectives. The number of samples carried out for this study is the population of Small Music Studio Business employees in Bandung. The analysis technique used is multiple regression analysis and descriptive analysis. The research limitations are limited sample size and data collection related to the object, which is categorized as small and medium enterprises (SMEs). The results indicate that organizational clan culture and democratic leadership style positively and significantly impact employee loyalty, either partially or simultaneously. The linkage between organizational clan culture and democratic leadership style toward employee loyalty shows a 70 percent correlation, and the rest of the value, 30 percent are affected by any other factors.